Penerapan Metode Omnibus Law Dikaitkan Teori Kemanfaatan Hukum Dalam Permasalahan Legislasi Lingkungan Hidup - Hassanain Haykal; Demson Tiopan; Theo Negoro (Ajudikasi : Jurnal Ilmu Hukum, 2021)
Environmental problems are very complex, one of which is related to the formation of laws and regulations in the environmental sector. The interrelated effect of the many regulations governing environmental problems raises not only legal problems, but also moral problems such as corruption and bribery. One of the efforts to solve environmental legislation problems is The Omnibus Law. The Omnibus Law itself often used by other countries to overcome chaos of the prevailing laws which are considered as too many and thus efficiency is in need to create legal certainty and to avoid overlapping between state institutions authority. This article is an analytical-juridical study regarding the application of the Omnibus Law metdhod to address legislative problems regarding the environment in Indonesia. This study uses a normative juridical approach with the data obtained from library research and literature related to the object being studied. The result of the study found that the Omnibus Law method can be used as a way to harmonize the laws and regulations regarding the environment in Indonesia with a note that it fosters a sense of awarnezss and a sense of belonging to the community towards legal product that use the Omnibus Law method as a means of ordering legislation.